Performance of a Large-Scale Excavation by Bottom-Up Technique in Hangzhou Soft Clay - Ri-qing Xu; Yi-hong Zhu; Pan Ding (Advances in Civil Engineering)
This paper studied the excavation of a foundation pit above a running subway tunnel in Hangzhou soft soil. The zoned excavation and top-down construction techniques were adopted to control the deformation caused by foundation pit excavation. The excavation was divided into four parts, named Zone A, B, C, and D. Zone A adopted temporary diagonal bracing, and the control effect of deformation was poor; it was cancelled and changed to rapid excavation and thicker cushion in Zones B, C, and D. During the whole construction process, the lateral displacement and settlement of the diaphragm wall, surrounding ground surface, and building settlement were monitored and analysed. The data showed that the lateral displacement of the diaphragm wall was effectively reduced by the zoned excavation technique, and the maximum lateral displacement value of the diaphragm wall in Zone A was the least; rapid excavation and reduced soil exposure time also could effectively control the deformation, and the lateral displacement of the diaphragm wall in Zone C is less than Zone B and Zone D. The ground settlement is strongly related to the lateral displacement of the diaphragm wall. In order to reduce the surrounding ground and building settlements, efforts should be made to reduce the wall lateral displacement.